2015
DOI: 10.1002/aoc.3261
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoparticles on dichromium trioxide: a highly efficient catalyst from copper chromium hydrotalcite for oxidant‐free dehydrogenation of alcohols

Abstract: Stable copper(0) nanoparticles supported on chromium (Cu(0)/Cr2O3) are prepared from the composite precursor copper chromium hydrotalcite. The resulting Cu(0)/Cr2O3 catalyst is first used in the selective dehydrogenation of alcohols to aldehydes. More impressively, these dehydrogenations are performed without oxidants and yields of products are high. The stability of Cu(0)/Cr2O3 is also assessed by studying its recoverability and reusability for up to five cycles. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Within the set of 14 samples, all catalysts exhibit a quantitative selectivity toward 2-octanone, in line with what have been reported for several metal supported heterogeneous catalysts, regardless of the metal used. 37,38,40,42,45,47,49,50,52,53,54 When the laurate was used as a ligand (first series of catalysts) the corresponding catalysts showed similar catalytic activity (conversion 32-35%) except short nanorods (L-R-3, conversion of 4%). In the second series, all Co nanoparticles protected by palmitate were poorly or not active towards 2-octanol dehydrogenation.…”
Section: Catalytic Activity Of Shaped Co Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the set of 14 samples, all catalysts exhibit a quantitative selectivity toward 2-octanone, in line with what have been reported for several metal supported heterogeneous catalysts, regardless of the metal used. 37,38,40,42,45,47,49,50,52,53,54 When the laurate was used as a ligand (first series of catalysts) the corresponding catalysts showed similar catalytic activity (conversion 32-35%) except short nanorods (L-R-3, conversion of 4%). In the second series, all Co nanoparticles protected by palmitate were poorly or not active towards 2-octanol dehydrogenation.…”
Section: Catalytic Activity Of Shaped Co Npsmentioning
confidence: 99%
“…33 Many different supported noble and non-noble metal catalysts were reported as active in this reaction, i.e. Pt, 34 Pd, 35 Ru, 36,37 Re, 38 Rh, 39 Au, 2,40,41 Ag, 42,43,44,45 Cu, 46,47,48,49 Ni 50,51 and Co. 52 Regarding the unsupported metal catalysts, Re NPs were reported as active towards acceptor-less alcohol dehydrogenation. 53 Also, we have recently shown that Co nanorods stabilized by carboxylate (laurate) ligands have good catalytic properties for this reaction, with a high chemoselectivity, towards a broad substrate scope including linear and cyclic alcohols and a good recyclability (3 runs with no decrease in activity and selectivity and no modification of the anisotropic shape).…”
Section: Introductionmentioning
confidence: 95%
“…Pt, [18] Pd, [19] Ru, [20,21] Re, [22] Au, [23][24][25] and Ag, [26][27][28][29][30] have been shown to be active towards acceptor-less alcohol dehydrogenation. Due to their higher abundancy and lower costs, non-noble metal catalysts have also been investigated, namely Cu, [31][32][33] Ni, [34,35] and Co [36] which proved to be also active. For most supported metal catalysts active in AAD reaction, the nature of the support is crucial for their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when oxygen is chosen as oxidant, volatile alcohols or organic solvents have the risk of burning or even explosion. [ 7 ] Anaerobic dehydrogenation of alcohols using olefins, ketones and N ‐oxides as hydrogen acceptors is an alternative method. [ 8 ] In view of environmental, economic and safety factors, catalytic dehydrogenation of alcohols to prepare carbonyl compounds in the absence of oxidants and hydrogen acceptors is an ideal and atom‐economic way.…”
Section: Introductionmentioning
confidence: 99%